2018
DOI: 10.3390/ijms19113428
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Induced YAP/TAZ Activity Mediates Leukocyte-Endothelial Adhesion by Regulating VCAM1 Expression in Endothelial Cells

Abstract: YAP/TAZ, a transcriptional co-activator of Hippo pathway, has emerged as a central player in vessel homeostasis such as sprouting angiogenesis and vascular barrier stabilization, during development. However, the role of YAP/TAZ in pathological angiogenesis remains unclear. Here, we demonstrated that YAP/TAZ is a critical mediator in leukocyte-endothelial adhesion induced by the vascular inflammatory cytokine TNF-α. YAP/TAZ was dephosphorylated, translocated from the cytosol to the nucleus, and activated by TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 39 publications
4
43
0
Order By: Relevance
“…Hippo-Yap plays important roles in regulating cell proliferation/death homeostasis and mediating tissue development or organ size 43 . It has been shown that Yap translocates to the nucleus and is activated in response to TNF-α in endothelial cells 44 . Gao et al 45 confirmed that TNF-α triggers IKK-mediated Yap activation in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hippo-Yap plays important roles in regulating cell proliferation/death homeostasis and mediating tissue development or organ size 43 . It has been shown that Yap translocates to the nucleus and is activated in response to TNF-α in endothelial cells 44 . Gao et al 45 confirmed that TNF-α triggers IKK-mediated Yap activation in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that among the genes that are differentially expressed by the two culture conditions we studied, some of them are regulated by YAP. In particular, Tnf, which we estimated to be downregulated in MSCs culture in the 3D Nichoid, are known to be regulated by YAP [ 51 ]. As far as genes upregulated by the 3D Nichoid, as compared to the flat surface, Lif, IL6, and BMPs are also known to be regulated by YAP [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upstream signaling pathways regulating YAP/TAZ activity have been shown to mediate cellular interactions with a broad range of microenvironmental factors including (i) soluble bioactive ligands ( Yu et al, 2012 ; Cai and Xu, 2013 ; Chen and Harris, 2016 ; Yang et al, 2019 ), (ii) biomechanical cues ( Dupont et al, 2011 ; Kim et al, 2011 ; Nardone et al, 2017 ; Pardo-Pastor et al, 2018 ), (iii) energy, osmotic and hypoxic stress ( DeRan et al, 2014 ; Ma et al, 2015 ; Mo et al, 2015 ), and (iv) inflammation and tissue injury ( Gregorieff et al, 2015 ; Kim H. B. et al, 2017 ; Choi et al, 2018 ; Flinn et al, 2019 ), via a diverse array of surface receptors, cytoskeletal elements and cytosolic signaling proteins, as illustrated in Figure 2 . Hence, by manipulating YAP/TAZ signaling, we can control how stem/progenitor cells change their phenotype in response to external stimulation and microenvironmental cues.…”
Section: Introductionmentioning
confidence: 99%